Coat Colour and Body Temperature Regulation in Indian Desert Goats - Goyal, Surendra P (Annals of Arid Zone, 2016)
A black coat colour appears to impart some thermolytic advantage over other coat colours in Rajasthan desert goats. The adaptive significance of the desert goat’s shade-seeking behaviour has been discussed.